Faktor-Faktor Yang Mempengaruhi Rendahnya Pemakaian KB Alat Kontrasepsi Dalam Rahim (AKDR) Di Puskesmas Talang Rimbo Lama Kabupaten Rejang Lebong Tahun 2022 - Diana Rizka Kusumawati; Murwati Murwati; Julius Habibi (Gayaku Publisher, 2022)
Based on data obtained from the Rejang Lebong District Health Office in 2021, the number of AKDR family planning acceptors such as IUDs was 32. This number is still very low when compared to hormonal family planning such as implants with 482 acceptors, injections with 16,004 acceptors, and pills with 7,720 acceptors. Meanwhile, the national target for active family planning participation in 2020 is 20.5%. Puskesmas Talang Rimbo Lama, Rejang Lebong Regency, is one of the health centres with low MDR participants in the last 3 years, namely in 2019 there were 6 acceptors, in 2020 there were 5 acceptors, and in 2021 there were 4 acceptors. Objective To know the factors that influence the low use of domestic contraceptives (IUD) at the Talang Rimbo Lama Health Centre, Rejang Lebong Regency, in 2022. descriptive quantitative research with analytical survey research methods using cross-sectional design. The sample in the study was 68 people using the accidental sampling technique. The research instrument used was a questionnaire sheet. The research analysis used univariate and bivariate analysis with the chi-square test. The results showed there was no relationship between parity (p = 0.648) and the low use of intrauterine contraceptives (IUD) at the Talang Rimbo Health Centre, Rejang Lebong Regency, in 2022. There is a relationship between knowledge (p 0.044) and husband support (p = 0.033) and the low use of intrauterine contraceptives (IUD) at the Talang Rimbo Health Centre, Rejang Lebong Regency, in 2022. Suggestions: It is necessary to explore the knowledge of respondents related to the incidence of diabetes mellitus so that field interventions to improve respondents' knowledge are more appropriate. It is necessary to conduct socialisation for PUS related to IUDs so that people understand the advantages and disadvantages of IUDs.